Imidazole/4,4 `-azopyridine bridging binuclear Ru(II) complexes: design, synthesis, bimolecular interactions and cytotoxicity against HeLa cell line - Khanvilkar, Priyanka; Dash, Soumya R.; Pulipaka, Ramadevi; Shirsath, Kavita; Devkar, Ranjitsinh; Chakraborty, Debjani (Journal of the Iranian Chemical Society, 2021)
Binuclear Ru(II)-arene complexes [(eta(6)-pcym)(Flq)Ru(mu-im/mu-azpy)Ru(Flq)(eta(6)-p-cym)]Cl (C1-C8) (cym = cymene; Flq = fluoroquinolones; im = imidazole; azpy = 4,4 ` azo pyridine) have been synthesized and characterized by elemental analysis, molar conductivity and various spectral techniques (ESI-MS, IR, UV-Vis and H-1-NMR). The geometry of the complexes was optimized by DFT calculations, which revealed a pseudo-octahedral coordination around each metal centre. Binding of the synthesized complexes with CT-DNA and BSA was studied spectroscopically, and it has been established that the presence of two hydrophobic planar arene moieties enhances the binding efficacies of the binuclear complexes to the macromolecules, compared to their mononuclear analogues. The results of competitive binding between C1-C8 and ethidium bromide (EB) towards DNA have shown that the complexes are able to displace EB from DNA-EB adduct and interact with DNA via intercalation. The complexes display cytotoxicity against the HeLa human cervical cancer cell lines with IC50 values in the range of 30.1-120.9 mu M.
Keywords: Binuclear ruthenium (II) complexes; BSA binding interactions; DFT calculations; DNA; Fluoroquinolones (FQs); HeLa human cervical carcinoma